Molecular improvement of alfalfa for enhanced productivity and adaptability in a changing environment. (10th November 2017) - Singer, Stacy D.; Hannoufa, Abdelali; Acharya, Surya
Abstract: Due to an expanding world population and increased buying power, the demand for ruminant products such as meat and milk is expected to grow substantially in coming years, and high levels of forage crop production will therefore be a necessity. Unfortunately, urbanization of agricultural land, intensive agricultural practices, and climate change are all predicted to limit crop production in the future, which means that the development of forage cultivars with improved productivity and adaptability will be essential. Because alfalfa ( Medicago sativa L.) is one of the most widely cultivated perennial forage crops, it has been the target of much research in this field. In this review, we discuss progress that has been made towards the improvement of productivity, abiotic stress tolerance, and nutrient‐use efficiency, as well as disease and pest resistance, in alfalfa using biotechnological techniques. Furthermore, we consider possible future priorities and avenues for attaining further enhancements in this crop as a means of contributing to the realization of food security in a changing environment. Abstract : As the demand for ruminant products is expected to escalate substantially in coming years, and alfalfa is one of the most widely cultivated perennial forage crops, an expansion in its production is going to be essential. Unfortunately, because various factors, including climate change, are predicted to limit crop production in the future, the development of alfalfa cultivars with improved productivity and adaptability will be a necessity. In this review, we discuss advancements that have been made in terms of the biotechnological enhancement of numerous traits in alfalfa that have the potential to result in improved crop yield, and consider future strategies for achieving a highly productive livestock industry in a changing environment.